Crashes on Financial Markets - Tran Dinh, Khanh; Stádník, Bohumil; Brodani, Jana; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2016)
The aim of this work is description and analysis of the phenomena which suddenly cause unexpected and sharp decline in the financial markets, called crashes or collapses. This work is divided into theoretical and practical part. The theoretical part deals with the definition of the financial market and its crash, in addition, this part provides an overview of the theories explaining the origin of the speculative bubble and its bursting. The object of practical part is to describe occurred events in the financial markets in order to determine the possible causes, circumstances and consequences of these crashes.
Vedoucí práce: Bohumil Stádník
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses